Prevalence of Hepatitis C Virus in Blood Donors (Medical Forum Monthly, 2024)
Objective: To determine the prevalence of hepatitis C virus in healthy blood donors. Study Design: A prospective descriptive study. Place & duration: This study was conducted in the Pathology Department Combined Military Hospital, Multan within 3 years from 01-07-2007 to 30-06-2010. Patients & method: A total of 18042 blood donors ranging from 18 – 55 years of age were screened for hepatitis C virus antibodies by ELISA method. Results: Hepatitis C virus antibodies were positive in 602 (3.3%) Conclusion: Seroprevalence of hepatitis C is high even in healthy young blood donors.